Analisis Faktor-faktor Yang Berpengaruh Pada Keputusan Pembelian Produk Kosmetik Halal - Eni Mulati; Budi Utomo (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2021)
The purpose of this research is to find out the influence of product knowledge, religiosity, and Islamic advertising ethics on purchasing decisions with purchase intention as intervening variable. Data was collected by distributing questionnaire to 100 respondents of consumers of Wardah product cosmetics in Salatiga with purposive sampling method. The data obtained were processed using SPSS 23 analysis tools. Based on the t-test, the results showed that partially product knowledge had no effect on purchasing decision, then religiosity partially had no effect on purchasing decisions. While consumer buying interest partially has a significant effect on purchasing decisions. Based on the results of the path analysis test, it show that buying interest doesn't have a mediating effect on the influence of religiosity on purchasing decisions. Then buying interest has a mediating effect on the influence of product knowledge and Islamic advertising ethics on each purchase decision.